The Disposal Mode of Maine’s Waste Governance - Blackmer, Travis; Berry, Brieanne; Haedicke, Michael; Isenhour, Cindy; Lee, Susanne; MacRae, Jean; Saber, Deborah; Victor, Erin (Maine Policy Review, 2023)
Maine’s materials management system is stuck in a disposal mode of waste governance. Despite significant investments in programs and policies designed to reduce the amount of waste the state buries each year, recent shocks and uncertainties have resulted in increased waste generation and disposal. This paper analyzes specific ways through which materials management in Maine has become locked in to a disposal mode of waste governance. We build a framework to help understand various forms of lock-in and how they might be unlocked. This framework is applied to the extended producer responsibility packaging law that is presently under the rule-making process in Maine, the first state to adopt such a policy in the United States.